Added interest at the fodder bank - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Fodder banks, which are planted pastures of forage legumes, were originally developed to provide dry-season feed for cattle in the subhumid zone of West Africa. Farmers are, however getting even greater benefits by using them for small ruminants...